A coordination language for agents interacting in distributed plan-execute cycles. (25th June 2009) - De Vries, W.; Meyer, J-J.Ch.; De Boer, F.S.; Van der Hoek, W.
An architecture is proposed for agents to coordinate formation and execution of plans. Along with the architecture, a new coordination language is introduced that agents may employ to form temporary alliances for planning and plan execution. This language is based on ideas from constraint programming and a formal operational semantics is given for it.